Acne in adult women and the markers of peripheral 3 alpha‐diol G activity. (6th June 2016) - Cunha, Marisa G; Martins, Carolina P; M Filho, Carlos D'Aparecida; Alves, Beatriz C A; Adami, Fernando; Azzalis, Ligia A; Fonseca, Fernando L A
Summary: Background: Acne in adult women is a frequent hard‐to‐manage disease with many relapse cases. It mostly interferes with the quality of life of patients, bringing them major metabolic and social losses. As androgenic hormones play a very important role in the acne pathogenesis, the early diagnosis of hyperandrogenic states is very useful for the proper evaluation of each patient and for a better choice of therapeutic management. Defining a pattern for laboratory profile analysis is important for the control of relapses of acne breakouts in adult women, which lately has been the aim of many published studies. Aim: To establish the relation between 3 alpha‐diol G levels and acne in female patients with normal androgenic status without menstrual dysfunctions. Patients/Methods: The evaluation of serum 3 alpha‐androstanediol glucuronide levels through an enzymatic immunoassay method (Androstanediol Glucuronide ELISA Kit) for a direct quantitative measurement in 26 patients with grade II and III acne, ages ranging from 13 to 50. Results: Among the analyzed patients, 83% had grade II acne, and among this total, 60% were aged 14 or over. According to age, 12 studied patients showed serum 3 alpha‐diol G levels within normal range and 11 patients had increased levels. Conclusions: A total of 60% of adult women with acne present increased levels of androgens and among those with normal levels and without menstrual dysfunctions, 50% show an increase in 3 alpha‐diol G. Therefore, a pharmacological approach with anti‐androgenic drugs for acne therapy in most of these patients is advisable.